TURNOVER INTENTION YANG DIMEDIASI OLEH KOMITMEN ORGANISASI (Studi Kasus PT. Pos Indonesia Kantor Cabang Pekalongan) - M. Ghusni Ridho; M. Farid Wajdi; Muhammad Sholahuddin (JURNAL ILMIAH EDUNOMIKA, 2024)
The research objective was to determine the effect of Job Stress and Satisfaction on Turnover Intention mediated by Organizational Commitment at the Pekalongan Post Office. This research was conducted at PT Pos Indonesia Pekalongan Branch. The number of respondents taken was 100 employees. Data analysis uses SmartPLS to test the validity, reliability and test the research hypothesis. The results of the study show that work stress has a significantly positive effect on Turnover Intention and a negative effect on Organizational Commitment. Job Satisfaction has no effect on Turnover Intention and has a positive effect on Organizational Commitment. Organizational Commitment has no effect on Turnover Intention. The results of path analysis testing on the indirect effect of both job stress and job satisfaction on switching intentions through organizational commitment did not show a significant relationship. Keywords: Job Stress, Job Satisfaction, Organizational Commitment, Turnover Intention